SCIENTIFIC AND METHODOLOGICAL FOUNDATIONS OF SPIRITUAL EDUCATION AND PROFESSIONAL ETHICS IN MEDICAL UNIVERSITIES (Modern American Journal of Social Sciences and Humanities, 2025)
The article analyzes historical documents, existing legislative norms and modern statistical data. In particular, the pedagogical methods proposed to increase the effectiveness of spiritual and moral education in medical universities are also considered.